A Microfluidic Aptamer-Based Sensor for Detection of Mercury(II) and Lead(II) Ions in Water - Wei-Hao Huang (MDPI AG, 2021)
Heavy metal contaminants have serious consequences for the environment and human health. Consequently, effective methods for detecting their presence, particularly in water and food, are urgently required. Accordingly, the present study proposes a sensor capable of detecting mercury Hg(II) and lead Pb(II) ions simultaneously, using graphene oxide (GO) as a quenching agent and an aptamer solution as a reagent. In the proposed device, the aptamer sequences are labeled by FAM and HEX fluorescent dyes, respectively, and are mixed well with 500 ppm GO solution before injection into one inlet of the microchannel, and the heavy metal sample solution is injected into another inlet. The presence of Hg(II) and Pb(II) ions is then detected by measuring the change in the fluorescence intensity of the GO/aptamer suspension as the aptamer molecules undergo fluorescence resonance energy transfer (FRET). The selectivity of these two ions is also shown to be clear among other mixed heavy metal ions. The experimental results show that the aptamer sensors have a linear range of 10~250 nM (i.e., 2.0~50 ppb) for Hg(II) ions and 10~100 nM (i.e., 2.1~20.7 ppb) for Pb(II) ions. Furthermore, the limit of detection is around 0.70 ppb and 0.53 ppb for Hg(II) and Pb(II), respectively, which is lower than the maximum limits of 6 ppb and 10 ppb prescribed by the World Health Organization (WHO) for Hg(II) and Pb(II) in drinking water, respectively.